Noninvasive detection of face perception characteristics in children with autism spectrum disorders1. (7th November 2013) - Gunji, Atsuko; Inagaki, Masumi
Abstract Children with autism spectrum disorders (ASD) have delayed or deviant social interaction and communication skills. Recent neuroimaging studies have corroborated unique behaviors and patterns of facial information processing in children with ASD, such as less attention toward faces, atypical gaze pattern and face inversion effect, and difficulty in understanding facial expressions and identification of faces. The findings suggest that these specific face recognition characteristics are the result of detail‐focused processing and/or a distinctive cognitive style in dealing with visual inputs. This paper reviews our recent work evaluating social perception of faces using noninvasive neuroimaging techniques in children with ASD.